2019
DOI: 10.30621/jbachs.2019.469
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Psychological Resilience and Social Support Levels in Hemodialysis Patients

Abstract: Purpose: This study was conducted to determine the relationship between psychological resilience and social support in hemodialysis patients in Turkey.Methods: This descriptive, comparative, cross-sectional, and correlational study was conducted with 100 patients who underwent hemodialysis treatment at a university hospital between September and December 2016. In the study, a questionnaire form including sociodemographic data as well as data regarding the disease, the Resilience Scale for Adults (RSA) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 15 publications
2
9
1
5
Order By: Relevance
“…In this study, those who remained active in the workplace (with very low representation in our sample) and above all retired individuals had lower levels of perceived stress than the unemployed or those engaged in domestic work, possibly due to better income (typically a protective factor against stress) and higher levels of activity and socialization (also protective against stress) [ 34 ]. The loss of resources has been found to be related to higher levels of perceived stress [ 35 , 36 , 37 , 38 ], emphasizing the importance of an intersectoral approach and social interventions to reinforce possible unfavorable situations in these patients [ 39 ]. With the results obtained in our sample, it was not possible to explain the fact that while employment status influenced stress, it did not affect resilience and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, those who remained active in the workplace (with very low representation in our sample) and above all retired individuals had lower levels of perceived stress than the unemployed or those engaged in domestic work, possibly due to better income (typically a protective factor against stress) and higher levels of activity and socialization (also protective against stress) [ 34 ]. The loss of resources has been found to be related to higher levels of perceived stress [ 35 , 36 , 37 , 38 ], emphasizing the importance of an intersectoral approach and social interventions to reinforce possible unfavorable situations in these patients [ 39 ]. With the results obtained in our sample, it was not possible to explain the fact that while employment status influenced stress, it did not affect resilience and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…As hypothesized, the results of this study indicated that better SES (higher education level and family income) contributed to a higher level of psychological resilience in maintenance hemodialysis patients, which supports the theory proposed by Wister et al ( 20 ). Maintenance hemodialysis patients with better SES might have more comprehensive understanding of the disease, adopt more effective problem-solving strategies, and have access to more information/health care services ( 39 , 40 ). Interestingly, the predictive utility of family monthly income was no longer significant when social support was included in the model, which indicates that the family financial level of maintenance hemodialysis patients may affect the psychological resilience through the role of social support.…”
Section: Discussionmentioning
confidence: 99%
“…Protective factors mediate and facilitate the positive adaptation of individuals to adversity and could be distinguished in those relating to individual characteristics, and those relating to environmental characteristics (Lakioti, 2016;Masten, 2001Masten, , 2007. The main protective factors against adversities are cognitive abilities, self-regulation (Masten & Obradovic, 2008;Masten & Wright, 2010), a positive self-image (Liu et al, 2014), optimism (Kleiman et al, 2017), coping strategies against stress (Kraemer et al, 2011;Mayordomo et al, 2016), experiencing positive emotions (Fredrickson et al, 2003;Meneghel et al, 2016) and positive relationships with others (Karadag et al, 2019;Sippel et al, 2015).…”
Section: Psychological Resiliencementioning
confidence: 99%